Marketing Challenges of Corporate Social Responsibility: Case Study of Mobile Telephone Operators in Ecuador - Bonilla Freire, Janeth; Chabusa Vargas , Jorge; Tello Caicedo, Grace; Cedeño Velasco, Alexander (Revista Universidad de Guayaquil, 2020)
This article integrates Corporate Social Responsibility CSR and marketing by analyzing how the marketing literature onCSR has been discussed by examining not only definitions as a first part. But also. the Marketing Challenges of Corporate Social Responsibility: Case Study of Mobile Telephone Operators in Ecuador. The methodology applied was the documentary and integral correlational. As a result. this analysis showed that the implementation of Corporate Social Responsibility Marketing strategies has an important influence on consumers. considering them as partners in the retribution to society through Social Responsibility marketing policies and strategies. This is confirmed with the result of the test in SPSS where the alternative hypothesisis accepted that the increase in mobile telephone lines was positively accused by the population growth in Ecuador.